Peasants and agro-chemicals in eastern Amazonia - Chaves, Genisson Paes; Magalhães, Sônia Barbosa (Desenvolvimento e Meio Ambiente, 2021)
This text analyzes how an Amazonian peasant society, integrated into the oil palm industry, makes sense and understands the use of agrochemicals within its social and symbolic universe. Through ethnographic field research we sought to understand how the peasant society of the São Vicente community, Moju village, state of Pará, weaves and constructs this relationship. Poison or chemicals are the names attributed to agrochemicals; while they are considered dangerous, their risks are relativized through socio-cultural mechanisms that are interposed between manufacturers’ recommendations, company posters and daily use. These also predominate within the progressive course of sickness, which is often silenced.